Penyelesaian Sengketa Ekonomi Syari’ah menurut Pengelola BMT IKPM Gontor Ponorogo - Aji Damanuri (Justicia Islamica, 2015)
Along with the development of shari'ah financial institutions in Indonesia, shari'ah banking problems are also increasingly occurring in Indonesia. The next problem that arises is who has the authority (competence) to resolve it? Is it the District Court (PN) or the Religious Court (PA)? Based on these problems, researchers are interested in examining; how is the understanding of BMT IKPM Gontor Ponorogo managers of the concept of shari'ah economic dispute resolution? And how are the forms of settlement of shari'ah economic disputes at BMT IKPM Gontor Ponorogo? This research took place at BMT IKPM Ponorogo because this BMT is among those trying to implement pure shari'ah financing with various kinds of problems that need further handling. The results of this study are; The concept of sharia economic dispute resolution according to the manager of BMT IKPM Gontor is built on the principle of helping and kinship, therefore deliberation and consensus are the main choices in resolving problems with customers, so that customers with problems are considered as people who must be helped, not people who are punished. Meanwhile, the forms of settlement of shari'ah economic disputes at BMT IKPM Gontor Ponorogo are in accordance with the principle of kinship because they are pursued through deliberation and as much as possible avoid bringing disputes into the realm of law. The forms of settlement carried out are in the form of debt scheduling, elimination of fines, and closing customer dependents with social funds taken from SHU.